Evaluation of climate change influence on non-point source pollution in the Sand River Catchment, Limpopo, South Africa - Chuene, Tlhogonolofatso Abram (My University, 2025)
Non-point source (NPS) pollution of freshwater resources is a major environmental concern as untraceable pollutants contribute to the deterioration of water quality which affects human, animal and environmental wellbeing and sustainability. This study evaluated the influence of climate change on NPS pollution in the Sand River Catchment (SRC). Excel statistical (XLSTAT, version 2023) Mann-Kendall and Sen’s slope trend analysis were employed to determine the historical trends in precipitation and minimum, maximum, and average temperature, using monthly timeseries data from October 1992 to September 2022. Soil and Water Assessment Tool plus (SWAT+ rev. 61) was set up, calibrated, validated, and used to simulate the monthly and annual sediment and nutrient constituents, Total Inorganic Nitrogen (TIN), and Total Inorganic phosphorus (TIP) loads in the SRC. The one-way analysis of variance (ANOVA) was used to determine the significance of the relationships between temperature and precipitation and the sediment, TIN, and TIP loads. SWAT+ was further used to implement and evaluate the performance of Best Management Practices (BMPs) (Vegetative Filter Strips (VFS), Grassed Waterways (GWW), and VFS+GWW on the pollution control in the SRC. The trend analysis results showed that there has been an insignificant (P > 0.05) steady increase in average and maximum temperature in the SRC. There was, however, a decrease in minimum temperature. Moreover, the results showed a significant (P < 0.05) decrease in precipitation in the same timeframe. The SWAT+ calibration and validation results showed that the statistical indices (NSE and R2 ≥ 0.72; –17.30 ≤ PBIAS ≤ 14.74) fell within an acceptable range with a good agreement between the observed data and the simulated output. The results of the assessment of the impact of climate change on the nutrient constituents of the basin confirmed the influence of average monthly temperature and precipitation on average monthly sediment, TIN, and TIP loads. The load decreased during low precipitation months and increased during high precipitation months. The average annual precipitation significantly (P < 0.05) decreased with a decrease in average annual sediment (R2 = 0.63), TIN (R2 = 0.73), and TIP (R2 = 0.55) load. However, average annual temperature significantly (P < 0.05) increased with a decrease in sediment (R2 = 0.23), TIN (R2 = 0.19), and an insignificant (P > 0.05) decrease in TIP (R2 = 0.05). The BMP results showed that the VFS was effective in retaining low sediment, TIN, and TIP loads at sub-catchment level and catchment level (27/23%, 23/20%, and 30/25%), respectively, compared to GWW (47/38%, 35/31%, and 43/31%), respectively. Moreover, the combination of VFS and GWW (VFS+GWW) effectively retained high loads of sediment, TIN, and TIP in sub-catchment level when compared to catchment level (70/58%, 66/56%, and 71/62%), respectively. The study concluded that climate change influences NPS pollution in the SRC, and BMPs can be employed to manage and control the agricultural NPS pollution within the catchment. Furthermore, implementing BMPs at sub-catchment level is the most effective management of NPS pollution in the SRC.
Thesis (M. Sc. (Geography)) -- University of Limpopo, 2025
Keywords: Best management practices; SWAT+ model; Trend analysis; Climate change; Non-Point source pollution; Sand river catchment; Global warming; Climatic changes; Water -- Pollution; Water quality -- South Africa -- Limpopo; Trend surface analysis